The role of exercise and NMNAT1 on functional and behavioural aspects of brain ageing in the mouse - Taylor, Helen Lynette (2019)
Ageing is a complex process that occurs in every living organism and is the result of interactions between genetics and the environment. As we age, the risk of developing a number of diseases like Alzheimer’s disease, cardiovascular disease and cancer increases significantly. However, not everyone will develop any of these illnesses, and may instead undergo ‘healthy ageing’, a process broadly defined in humans as “ageing in the absence of illness”. Healthy ageing can be promoted by, amongst other things, regular exercise and caloric restriction. Previous research has shown that caloric restriction can delay the onset of the negative impacts of ageing, and also extend maximum lifespan. These effects are regulated via the activity of the NAD+ dependent deacetylase SIRT1, and overexpression of SIRT1 can have the same effect as caloric restriction. Exercise also promotes improved health with ageing, thought the underlying mechanisms are not fully understood.